2014
DOI: 10.1037/law0000006
|View full text |Cite
|
Sign up to set email alerts
|

Do they matter? A meta-analytic investigation of individual characteristics and guilt judgments.

Abstract: Many people believe the personal attributes of trial participants substantially impact the decisions of juries, and considerable research has examined the extent to which characteristics of jurors and defendants are associated with juror judgments of guilt. To assess this broad issue, we meta-analyzed empirical studies examining the relationship between 11 juror and defendant characteristics and individual-level judgments of guilt in criminal trial contexts. Three potential moderator variables were also invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
196
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(223 citation statements)
references
References 257 publications
11
196
2
4
Order By: Relevance
“…We examined multiple factors in our model; therefore, it is possible that victim gender did not account for a significant portion of the variance in credibility scores or verdict decisions while competing with all other direct and indirect effects. In light of Devine and Caughlin's (2014) meta-analysis, we view our null effects as evidence that there were stronger factors in our model (e.g., prior opinions about children's eyewitness abilities), and that previous findings attributing effects to victim gender may not have accounted for these other factors. These factors likely interrelate or interact with one another, and impose indirect, rather than direct, effects on guilt decisions.…”
Section: Child Age and Gendermentioning
confidence: 74%
See 1 more Smart Citation
“…We examined multiple factors in our model; therefore, it is possible that victim gender did not account for a significant portion of the variance in credibility scores or verdict decisions while competing with all other direct and indirect effects. In light of Devine and Caughlin's (2014) meta-analysis, we view our null effects as evidence that there were stronger factors in our model (e.g., prior opinions about children's eyewitness abilities), and that previous findings attributing effects to victim gender may not have accounted for these other factors. These factors likely interrelate or interact with one another, and impose indirect, rather than direct, effects on guilt decisions.…”
Section: Child Age and Gendermentioning
confidence: 74%
“…Recently, a meta-analysis of factors influencing guilt decisions indicated that participant characteristics (e.g., gender) may not have as strong an effect as case or trial characteristics (e.g., sexual abuse case vs. robbery case) or may have a moderated or mediated effect on verdicts (Devine & Caughlin, 2014). We therefore chose SEM to model our predicted pathways and to account for their simultaneous association with one another as well as the direct and indirect effects on mock jurors' guilt decisions.…”
Section: Analytical Planmentioning
confidence: 99%
“…Este aspecto se podría paliar con estudios de casos en vez de sentencias, en los que se sigue el proceso de cada acusado individualmente. Por otra parte, también sería interesante ampliar el número de variables a estudiar, y tener en cuenta aspectos como la pertenencia a minorías étnicas de acusados y/o víctimas (Devine y Caughlin, 2014), el estado civil del acusado, o incluso las características personales o ideológicas de Jueces y Magistrados (Arce, Tortosa, y Alfaro 2003).…”
Section: Discussionunclassified
“…En relación a los antecedentes penales, un meta-análisis reciente (Devine y Caughlin, 2014) refleja que el conocimiento del historial criminal previo aumenta las probabilidades de condena (r =.12). Utilizar la información de los antecedentes como indicador de probabilidad o pronóstico de un hecho, conlleva serios peligros.…”
unclassified
See 1 more Smart Citation